Physiological study Of Agnimandhya (Dyspepsia) Due to Raktkshaya (depletion of blood tissue) - meena, Meenakshi; sharma, Rajesh kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Agni is an important component of the body considering its role in sharir dharan as well as in origin of disease. Out of seven dhatus, Raktdhatu(blood tissue) plays an important role in maintenance of agni It was found that pittakshaya associated with raktkshaya (depletion of blood tissue)can be considered as the possible cause of this. It is usually to notice that rakt dhatu kshaya Raktkshaya (depletion of blood tissue) leads to agnimandya (dyspepsia). Sour rasa is predominant in teja mahabhuta. It is needed for waned rakta(blood) to regain it physiological status. This mahabhuta with the help of correcting bhutagni of raktadhatu (blood tissue) corrects status of waned raktadhatu. (blood tissue) This is the reason sour such person desires taste.